Juridical Analysis Of Perpetrators Participating In Child Trafficking Crimes (Tppo) As Victims - Juwita, Siti Putri; Jayadi, Hendri; Hutahaen, Armunanto (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Human trafficking, particularly involving children, remains a persistent and complex challenge for the Indonesian legal system. Despite the enactment of Law Number 21 of 2007 on the Eradication of the Crime of Trafficking in Persons and related regulations, gaps persist in addressing individuals who simultaneously occupy the roles of perpetrator and victim. The urgency of this study arises from the increasing number of coerced participants being criminalized, which undermines substantive justice and human rights protections, highlighting the need for a normative and context-sensitive legal framework. This research aims to analyze the juridical accountability of individuals involved in child trafficking while experiencing victimization, evaluating the extent to which the current legal system aligns with principles of justice, legal certainty, and expediency. The research employs a qualitative approach with a normative juridical method, combining statute and conceptual analyses. Data were collected through comprehensive document review, including primary legal materials, academic literature, and international conventions, and were analyzed using qualitative juridical interpretation to examine the alignment between statutory provisions and ethical, social, and restorative justice considerations. Findings indicate that the Indonesian legal system often treats coerced individuals as full perpetrators, reflecting a gap between formal law and moral justice as articulated in Radbruch’s legal philosophy. Judicial practices are inconsistent, and institutional coordination is weak, limiting the effectiveness of law enforcement and rehabilitative mechanisms. Comparative insights from the United Kingdom and the Philippines reveal that explicit recognition of coerced participants as victims enhances both justice and law enforcement effectiveness. The study recommends legal reforms incorporating restorative justice principles, codification of non-punishment for coerced participants, judicial training, and institutional integration with social support services to ensure equitable, humane, and effective legal responses.